Role of surgery combined with kinase inhibition in the management of gastrointestinal stromal tumor (GIST) - Hohenberger, Peter; Eisenberg, Burton (Annals of surgical oncology, 2010)
Surgery is the standard treatment for primary, gastrointestinal stromal tumor (GIST); however, surgical resection often is not curative, particularly in large GIST. Five years after complete removal of their tumor, approximately half of treated patients relapse. Imatinib, an oral tyrosine kinase inhibitor (TKI), is first-line treatment in patients with metastatic or unresectable GIST. It has resulted in durable objective responses or stable disease in 84% of patients and is well tolerated. The efficacy of imatinib in advanced GIST has created interest in a variety of potential multimodal approaches to management that combine surgery with systemic therapy.